Hemostasis as an Evolutionary Development - Quick, A. J (Thrombosis and Haemostasis, 1967)
Hemostasis is a complex physiological mechanism that has evolved as the organism increased in complexity and the need for safeguarding against loss of blood became progressively greater. The most primitive phase is vascular contraction which sufficed until the cardiovascular system made greater demands on the need for protection against hemorrhage. The developing of a coalescing blood cell constituted the second major advance in the mechanism of hemostasis, and it is very probable that the thrombocytes of avian and reptile blood and the platelets of mammalian blood represent the evolutionary end products of this phase. The clotting mechanism is the last step and is the third line defense against hemorrhage. Even in the higher forms of life including man, none of these steps in hemostasis have been supplanted, but rather have been supplemented. Therefore residua of the primary step are not only present but still functioning. To understand the problem of bleeding, it must be viewed from the global aspect of hemostasis.